Kepemimpinan Pendidikan Transformatif untuk Mewujudkan Lingkungan Pembelajaran yang Inklusif dan Berkeadilan - Juwita; Arini Nuora Darina; Tiara Nurul Annisa'; Misbahul Arifin (Educational Research Center, 2025)
This study focuses on the role of transformative educational leadership in realizing an inclusive and equitable learning environment at the Islamic-based junior high school level. In the context of increasing student diversity and demands for an equitable education system, transformative leadership is key to creating responsive and participatory school culture change. This study uses a qualitative approach with a case study method implemented at SMPI Miftahul Ulum Besuki. Data collection techniques include in-depth interviews, observation, and documentation. The results of the study show that principals and teachers play a strategic role in internalizing inclusive values through institutional vision, teacher training, and adaptation of learning strategies that are tailored to students' needs. An open, empathetic and collaborative school culture is a true reflection of transformative leadership. The implications of this study emphasize the importance of strengthening the leadership capacity and collaboration of all school elements as a foundation for fair and competitive learning in the future.